The new Brazilian Space: Amazônia Azul and its implications | O novo espaço brasileiro: Amazônia Azul e suas implicações - Wiesebron, Marianne L. (Revista Brasileira de Estudos Urbanos e Regionais, 2017)
A Brazilian Admiral coined the concept Amazônia Azul or Blue Amazon, to draw attention to the incredible size of the country’s jurisdictional waters and to all the resources they contain, living, mineral including offshore oil and gas. These waters represent nearly 4.5 million km2 , which equals over 50% of the country’s land surface. However, to create this space with this enormous size, the Brazilian Interministerial Commission for Sea Resources (CIRM), coordinated by the Navy, had to be quite ingenious to follow the rules of the United Nations Convention on the Law of the Sea (UNCLOS). This article studies first the establishment of the space Amazônia Azul, then how this space is being developed in a sustainable way, and how its defence is being set up. The policies of defence created by the Lula Government are also quite innovative, and, in particular, the technology transfer with strategic military partners warrants special attention.